2010
DOI: 10.1016/j.ijbiomac.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin as an oxidative stress biomarker in the eye

Abstract: Identification of biomarker proteins in the retina and the retinal pigment epithelium (RPE) under oxidative stress may imply new insights into signaling mechanisms of retinal degeneration at the molecular level. Proteomic data from an in vivo mice model in constant light and an in vitro oxidative stress model are compared to controls under normal conditions. Our proteomic study shows that prohibitin is involved in oxidative stress signaling in the retina and RPE. The identity of prohibitin in the retina and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 22 publications
1
62
1
Order By: Relevance
“…A narrow range of isoelectric focusing was performed for the analysis of vimentin modifications (Figure 5B). Previously, we presented data from in vivo model from other genetic background (C57BL/6J) under constant light (7 days), intense light (7000-10,000 lux), or circadian regulated (12 h light/12 h dark) as well as C3HeB/FeJ model [1,3,33]. Prohibitin signaling and cytoskeletal protein expressions are consistent in mice model with two different genetic background (BL6 vs C3He), however, only albino mice showed different prohibitin/cytoskeletal protein expressions (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A narrow range of isoelectric focusing was performed for the analysis of vimentin modifications (Figure 5B). Previously, we presented data from in vivo model from other genetic background (C57BL/6J) under constant light (7 days), intense light (7000-10,000 lux), or circadian regulated (12 h light/12 h dark) as well as C3HeB/FeJ model [1,3,33]. Prohibitin signaling and cytoskeletal protein expressions are consistent in mice model with two different genetic background (BL6 vs C3He), however, only albino mice showed different prohibitin/cytoskeletal protein expressions (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…We have focused on understanding the cell death mechanism of the retina and RPE under oxidative stress [Chung et al, 2009;Lee et al, 2010a;Lee et al, 2010b;Zhang et al, 2010;Lee et al, 2011;Arnouk et al, 2011;Sripathi et al, 2011]. Our studies demonstrated that oxidative stress may trigger induction of anti-apoptotic erythropoietin, JAK2, and BCL-xL, as well as pro-apoptotic caspases.…”
Section: Phosphorylation Signaling In the Rpementioning
confidence: 99%
“…This approach demonstrated that prohibitin is involved in oxidative stress signaling in vitro and in vivo [Lee et al, 2010b;Arnouk et al, 2011;Srinivas et al, 2011]. Prohibitin was proposed as an anti-proliferative protein or a tumor suppressor forming a high molecular complex with prohibitin2 in mitochondria [Steglich et al, 1999].…”
Section: Anti-apoptotic Prohibitin Function In Mitochondriamentioning
confidence: 99%
“…Prohibitin is an inhibitor of cell cycle progression and may therefore contribute to the onset of wound's chronic phenotype. (Mishra et al, 2010;Lee et al, 2010;Dong et al 2010). This expression profile became progressively inverted going through deeper cells layers (Fig.…”
Section: Responding Granulation Tissue Develops From the Deep Layers mentioning
confidence: 99%